Carbon emissions from agricultural land use in China: spatio-temporal dynamics and pathways to neutrality - Shi, Xiongtian; Zhou, Zhenghao; Yu, Zhengyong (Frontiers in Environmental Science, 2025)
This research analyzes the spatio-temporal evolution and driving factors of agricultural land use carbon emissions (ALUCE) in China from 2013 to 2022, utilizing LMDI and STIRPAT models. Key findings include: (1) Significant regional disparities exist, with eastern provinces exhibiting high and increasing ALUCE levels, while western provinces remain low and stable, necessitating targeted regional strategies and technological support. (2) Total ALUCE in China decreased by 8.6%, highlighting the need to optimize high carbon emission sources for sustainable agriculture. (3) ALUCE inequality is stable yet slightly variable, driven by inter-provincial differences, with spatial polarization evident. (4) Agricultural production efficiency inhibits ALUCE, while output increases and labor scale positively contribute. A novel environmental organizational framework is proposed to reduce ALUCE, offering policy implications for developing countries focused on regional strategies, technical support, and sustainable practices.